Triple Hybrid (TriHy): What Happened When COVID Hit the Research Study - Ildiko Porter-Szucs; Barry DeCicco (Centre National d'Enseignement à Distance, 2024)
This study examines whether student achievement in a Master's degree course (Teaching English to International Learners - TESOL) on assessment is comparable regardless of the chosen participation modality for this "Triple Hybrid" (or "TriHy") course. The three delivery modes for this course were face-to-face (F2F), synchronous online (SO), and asynchronous online (ASO). The study began in January 2020, before the COVID-19 pandemic reached the university. For the first ten weeks, the course was taught as originally scheduled, but due to the interruption of face-to-face classes at the university, this group had to join the Synchronous Online (SO) group for the last five weeks of the semester. Although differences in student achievement in the course were not statistically significant, perceptions of factors that contributed to students' personal success were. We can conclude that the quality of teaching is not compromised in a Triple Hybrid format with considerable institutional support, significant commitment from teachers, including their time, and thoughtful student choices.